The association between park facilities and the occurrence of physical activity during park visits. (20th October 2018) - Stewart, Orion Theodore; Moudon, Anne Vernez; Littman, Alyson; Seto, Edmund; Saelens, Brian E.
Abstract: Prior research has found a positive relationship between the variety of park facilities and park-based physical activity (PA) but has not provided an estimate of the effect that additional different PA facilities have on whether an individual is active during a park visit. Using objective measures of park visits and PA from an urban sample of 225 adults in King County, Washington, we compared the variety of PA facilities in parks visited where an individual was active to PA facilities in parks where the same individual was sedentary. Each additional different PA facility at a park was associated with a 6% increased probability of being active during a visit. Adding different PA facilities to a park appears to have a moderate effect on whether an individual is active during a park visit, which could translate into large community health impacts when scaled up to multiple park visitors.